Pemberdayaan Ibu-Ibu Rumah Tangga Berbasis Gender melalui Pelatihan Membatik dalam Meningkatkan Ekonomi Keluarga oleh Kelompok Batik Marunda di Rusun Marunda Cilincing Kota Jakarta Utara - Permata, Della; Sholih; Siregar, Herlina (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research aims to describe (1) the stages of empowering household women based on gender through batik training by the Marunda Batik Group (2) the results of increasing family income among member women of the Marunda Batik household. The approach used in this research is qualitative descriptive method. Data collection techniques used are observation, interviews, and documentation. The data sources of this study consist of 11 individuals, namely 1 person as the program manager or chairperson and 10 women household artisans in Marunda Batik at Rusun Marunda Cilincing, North Jakarta. The results of this study indicate that: (1) the stages of empowering household women based on gender through batik training by the Marunda Batik Group consist of preparation stage, assessment stage, planning stage, formulation of action plan stage, implementation stage, evaluation stage, and termination stage (2) the results of increasing family income among women household artisans in the Marunda Batik Group can help women in increasing family economic income but have not brought significant changes to the needs of women household. Although basic needs, security, and social activities have been fulfilled, they have not shown initiative in developing their batik motif ideas. Nevertheless, the need for self-actualization has been fulfilled through the education provided to their children.